THE RESULTS OF THE STUDY COLLECTION OF THE SPECIES OF ASTRAGALUS IN ZABAYKALSKY KRAI - V. P. Makarov (Труды по прикладной ботанике, генетике и селекции)
In the article the results of studies of species of the genus Astragalus L. in the Zabaykalsky Krai in terms of collector's nursery. The characteristic of the species and specimens of Astragalus in winter hardiness, yield of green mass, foliage plants, nutrition of the forage, seed yields and sowing qualities of seeds.